New developments of computer services infrastructure in Wrocław University Library - Olszak, Rafał (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article presents new developments of computer services infrastructure in Wrocław University Library, such as power supply, core cables, and active equipment, as well as solutions for mass memory connected with the Library's task realization. The universality and necessity of their implementation were indicated in the context of the Library's present and future needs.
Keywords: switch; LAN - local area network; blade server; data center; structured cabling; storage